Considerations for Designing Accessible Educational Scenario-Based Assessments for Multiple Populations: A Focus on Linguistic Complexity - Oliveri, Maria Elena (Frontiers in Education, 2019)
As the diversity of the test-taker population increases so should assessment development practices evolve to consider the various needs of the multiple populations taking the assessments. One need is the ability to understand the language used in test items and tasks so they do not present unnecessary challenges for the test-takers, which may be misconstrued as a lack of knowledge of the content assessed. This investigation is important because linguistic complexity may constitute a source of construct-irrelevant variance, which may render an assessments’ passages and questions less accessible and present unnecessary challenges to the multiple test-taker populations potentially leading to score misinterpretation, disengagement with the task, and increased cognitive load. To develop more linguistically accessible assessments for multiple populations, less accessible construct-irrelevant text may require modification and less accessible construct-relevant text may need scaffolding. In this paper, I discuss considerations for designing accessible assessments for multiple populations with a focus on linguistic complexity. To illustrate these considerations, I refer to digitally delivered scenario-based tasks of English Language Arts framed in a science context.